PENGARUH PENGGUNAAN DANA DESA DAN BADAN PERMUSYAWARATAN DESA (BPD) TERHADAP KESEJAHTERAAN MASYARAKAT (Studi Kasus Desa Lancang Barat Kecamatan Dewantara 1 Kabupaten Aceh Utara) - neni triana; Irfan; miswar (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2022)
The village is a representation of the smallest legal community unit that has existed and has grown in line with the history of Indonesian people's lives and has become an integral part of the structure of Indonesian social life. As a form of village recognition by the state, especially in the context of clarifying the functions, duties, responsibilities and authorities of the village, as well as strengthening the position of the village and rural communities as subjects of development. The village is not just an object of development but is now a subject for building welfare (Mondong, 2013). Law Number 6 of 2014 confirms that the government's commitment to developing villages is to become independent and democratic, so that they can bring new hopes to social life. However, not a few people are worried about the management of Village Funds. In this study researchers will examine the Use of Village Funds and Village Consultative Body (BPD) for Community Welfare in Lancang Barat Village, Dewantara District, North Aceh. The population in this study is the government of Lancang Barat Village consisting of the keuchik, secretary, tuha peut, tuha lapan, Kaur and the community concerned. The population in Lancang Barat Village is 7,000 people, with the sampling method using the Slovin method so that the number of research samples is 300 people. Data analysis was carried out using a questionnaire and analyzed with SPSS. The results of the study found that the Village Fund had a positive and significant effect on community welfare. Providing Village Funds is a form of fulfilling village rights to carry out its autonomy so that it grows and develops following the growth of the village itself based on diversity, participation, autonomy, democratization, community empowerment can increase the role of the Village Government in providing services and improving community welfare. The Village Consultative Body has a positive and significant effect on improving community welfare. Village Community Welfare is a process in which village community members initially discuss and determine their wishes, then plan and work together to fulfill their wishes. Key Words: Village Fund, Welfare